The Dark Side of Dharma Why Have Adverse Effects of Meditation Been Ignored in Contemporary Western Secular Contexts? - Lutkajtis, Anna (2019)
In contemporary Western society, meditation techniques that were previously taught within the context of Eastern religious traditions are now increasingly being practiced in secular settings. While the boundary between the secular and the religious is blurred, popular meditation techniques such as Transcendental Meditation, vipassana, and mindfulness are generally promoted as being derived from Eastern religions, but inherently non-religious, aligned with Western psychology, and suitable for a general audience. Over approximately forty years, thousands of research studies suggest that there are many psychological and physiological benefits associated with these forms of meditation; however, a small but growing literature indicates there could also be adverse effects. In Eastern religious traditions, difficulties associated with meditation are acknowledged, and are usually understood to be milestones on the path to enlightenment, the result of improper practice, or due to individual differences. However, in a Western secular context, negative effects associated with meditation have largely been overlooked. This article argues that this is in part due to the fact that in contemporary Western society the goal of meditation has shifted from enlightenment to symptom relief and personal transformation, leading to the assumption that meditation is harmless and 'good for everyone'.
Keywords: Buddhism; Meditation; Mindfulness; Psychology